2016
DOI: 10.1007/s10340-016-0739-6
|View full text |Cite
|
Sign up to set email alerts
|

An invader supported by a parasite: Mistletoe berries as a host for food and reproduction of Spotted Wing Drosophila in early spring

Abstract: The Spotted Wing Drosophila (SWD), Drosophila suzukii Matsumura, an invasive pest species in Europe and the Americas, is able to feed and reproduce on numerous fruit crops and a wide range of wild host plants. SWD is thought to overwinter outside of agricultural fields in forests and hedges. To identify overwintering sites and early spring oviposition hosts, traps were installed in forests. In spring 2015, traps in the canopy of pine trees parasitized by mistletoe, Viscum album subsp. laxum, captured significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
44
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 36 publications
(48 reference statements)
6
44
0
3
Order By: Relevance
“…Drosophila suzukii was found commonly in five wild hosts that are present in the habitats surrounding blueberry fields in central and west‐central Michigan across two growing seasons (Table ). This pest is highly polyphagous and is known to utilize a variety of wild hosts, many of which were not found in the present study (Lee et al ., ; Poyet et al ., ; Briem et al ., ; Kenis et al ., ; Thistlewood et al ., ). We expect that the wild hosts sampled are only a fraction of the hosts available to D. suzukii in our landscape and these data do not represent the complete host range of wild fruits.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Drosophila suzukii was found commonly in five wild hosts that are present in the habitats surrounding blueberry fields in central and west‐central Michigan across two growing seasons (Table ). This pest is highly polyphagous and is known to utilize a variety of wild hosts, many of which were not found in the present study (Lee et al ., ; Poyet et al ., ; Briem et al ., ; Kenis et al ., ; Thistlewood et al ., ). We expect that the wild hosts sampled are only a fraction of the hosts available to D. suzukii in our landscape and these data do not represent the complete host range of wild fruits.…”
Section: Discussionmentioning
confidence: 98%
“…Honeysuckle and other wild hosts that bear fruit before berry crops ripen (e.g. mistletoe, Briem et al ., ) may serve as important drivers in the local abundance of D. suzukii and should be evaluated for their role in the ecology of this new pest on farmland.…”
Section: Introductionmentioning
confidence: 99%
“…The worldwide distribution of the SWD and of its economic importance has been recently reviewed by Asplen et al . The major factors affecting the population dynamics of D. suzukii include temperature and humidity, the availability of essential food resources, and the presence of effective biological control agents …”
Section: Introductionmentioning
confidence: 99%
“…Border sprays can be useful against pests that migrate from surrounding environments (Chouinard et al 1992;Trimble and Solymar 1997;Blaauw et al 2015);. Although we did not evaluate fly presence in surrounding areas or migration in this study, D. suzukii has been shown to utilize wild hosts in wooded areas surrounding blueberries, blackberries and raspberries (Lee et al 2015b;Liburd et al 2015;Briem et al 2016) and as a result, can increase pressure on adjacent crops (Klick et al 2016). Klick et al (2016) found that D. suzukii captures were higher in raspberry fields that were adjacent to wild 'Himalaya' blackberry (Rubus armeniacus Focke) than fields that were not in close proximity.…”
Section: Discussionmentioning
confidence: 86%